2017
DOI: 10.4174/astr.2017.92.1.35
|View full text |Cite
|
Sign up to set email alerts
|

Fortune of temporary ileostomies in patients treated with laparoscopic low anterior resection for rectal cancer

Abstract: PurposeThe current study aims to analyze the risk factors for the failure of ileostomy reversal after laparoscopic low anterior resection for rectal cancer.MethodsAll patients who underwent a laparoscopic low anterior resection for rectal cancer with a diverting ileostomy between 2007 and 2014 were abstracted. The patients who underwent and did not undergo a diverting ileostomy procedure were compared regarding patient, tumor, treatment related parameters, and survival.ResultsAmong 160 (103 males [64.4%], mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 25 publications
0
8
0
1
Order By: Relevance
“…Furthermore, 16% of cases in which DS is used cannot receive stoma reversal, the patient must therefore live with stoma permanently. 4 Studies have reported male sex, low anastomosis, preoperative chemoradiation, advanced tumor stage, one perioperative bleeding, and multiple firings of linear stapler as risk factors for AL after laparoscopic anterior resection (AR) with total mesorectal excision (TME) for rectal cancer. [5][6][7] Blood flow disorder at the anastomosis site has also been reported to be a risk factor, but still there has been no method to evaluate blood flow of the anastomosis-site, and sufficient analysis could not be performed.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, 16% of cases in which DS is used cannot receive stoma reversal, the patient must therefore live with stoma permanently. 4 Studies have reported male sex, low anastomosis, preoperative chemoradiation, advanced tumor stage, one perioperative bleeding, and multiple firings of linear stapler as risk factors for AL after laparoscopic anterior resection (AR) with total mesorectal excision (TME) for rectal cancer. [5][6][7] Blood flow disorder at the anastomosis site has also been reported to be a risk factor, but still there has been no method to evaluate blood flow of the anastomosis-site, and sufficient analysis could not be performed.…”
Section: Introductionmentioning
confidence: 99%
“…reported a non‐closure rate of 35% in patients who acquired a leak . A large population study by Haksal et al . established anastomotic stricture (54%) and patient refusal (16.7%) as reasons for non‐reversal.…”
Section: Discussionmentioning
confidence: 99%
“…In his article from 2008, Brian RK has described early postoperative complications that can occur and influence not only the morbidity and mortality of the patient, but [11]. Matthiessen et al reported that for 10.3% of all patients who had a lower anterior resection and a protective ileostomy, the presence of an anastomotic fistula has delayed the reestablishment of the intestinal continuation with up to 50 months [24].…”
Section: Postoperative Complications Linked To the Ileostomymentioning
confidence: 99%
“…The same study by Haksal M. et al stated that three of their patients had additional urinary problems (fistula, nephrostomy and/or urinary incontinence) that needed to be addressed before the closure of the ileostomy due to advanced (clinical T4) initial disease. The closure of their ileostomies was postponed due to a potential need of further medical or surgical treatments [11]. while the average interval before the ileostomy closure grew by 50 days [19].…”
Section: Other Medical/surgical Interventionsmentioning
confidence: 99%
See 1 more Smart Citation